Airline Customers Conflict Resolution in The Framework of Legal Protection For Consumers in Indonesia - Fauzi, Wetria (Universitas Ekasakti, 2023)
Aviation related issues include low supervision of airlines in Indonesia, the condition of aircraft that are old and less feasible and high rates of flight accidents. Management negligence and mistakes reach a level that endangers state security. An airline is an organization that provides flight services including cargo to passengers. They provide these services and form cooperation or alliances with other airlines for mutual benefit. However, the relationship between customers and airlines can sometimes lead to ruthless legal battles and violent conflicts. This paper discusses legal protection for airline customers in Indonesia. It seeks to investigate not only the legal arrangments regarding air transportation in Indonesia but mechanism to minimize/prevent disputes between consumers and airlines. Consumer dispute resolution with airlines refers to the Consumer Protection Act and Aviation Law. The research reveals that consumer-airlines conflicts can be resolved outside of the court through several dispute resolution models, including Consumer Dispute Settlement Agency, Non-Governmental Consumer Protection Agency, the Directorate of Consumer Protection agreed by the parties, based on Article 1338 of the Civil Code. This paper also show that it is necessary to make a simple dispute resolution system specifically for airline consumers in the form of an airline consumer dispute resolution assembly or a special arbitration agency.